What’s law got to do with it? Comparing the failure to deter or convict rapists in the United Kingdom and South Africa - Wykes, Maggie; Artz, Lillian (International review of victimology, 2020)
The journey from reporting rape to convicting rapists is complex, leading to high attrition and non-conviction rates. After wide consultation, the law in England and Wales was revised in 2003 to try to secure more convictions. In South Africa, a similar process occurred to produce a new law in 2007. Nonetheless, reported rapes have risen and conviction rates have fallen in both jurisdictions and it has been suggested that the failure of the criminal justice system to deal with ‘rape…encapsulates the sheer inadequacy of the law’ (Wykes and Welsh, 2009: 111) and offers little hope of justice to victims and little deterrence to perpetrators. In South Africa little has changed, except more is known about ‘the lived experiences of sexual violence’ (Artz and Smythe, 2007: 17) and more support is offered to victims after the event. This article explores the part played by law in dealing with rape, through a comparison of the UK and South Africa. Critical gendered analysis of their respective rape laws leads to the conclusion that that law cannot work effectively to deter or convict rapists: only men’s willingness to change can stop rape.